Supportive employment practices: perspectives of autistic employees. Issue 1 (11th February 2021) - Hedley, Darren; Spoor, Jennifer R.; Cai, Ru Ying; Uljarevic, Mirko; Bury, Simon; Gal, Eynat; Moss, Simon; Richdale, Amanda; Bartram, Timothy; Dissanayake, Cheryl
Abstract : Purpose: Employment can make an important contribution to individual well-being, for example, by providing people with a sense of purpose; however, autistic individuals face significant barriers to entering the workforce. This is reflected in high levels of underemployment and unemployment, with an estimated 80% of autistic people unemployed worldwide. This is higher than both other disability groups and people without disabilities. Research is needed to identify strategies that facilitate the sustained employment of autistic adults. This study aims to examine the perspectives of autistic individuals participating in a specialized employment program within the information and communication technology sector. Design/methodology/approach: Three focus groups were conducted with nine adults on the autism spectrum. Data were analyzed using an inductive approach according to established guidelines, which included coding and categorizing data into themes. Findings: Focus group analysis revealed four themes: trainees' previous work experiences; expectations of the employment program; recruitment and selection processes; and training and transition. Several factors associated with the changes to the recruitment and selection process were found to benefit the autistic employees. Originality/value: Few studies have characterized the work experiences of adults on the autism spectrum. Tailored employment processes that challenge traditional human resource management practices can increase the participation of autistic individuals in the workforce. Strategies for promoting the success of these programs are discussed.